Indonesian Political Ideology: Political Parties and Local Governance in Yogyakarta Municipality 1998-2015 - Al-Hamdi, Ridho (Tectum Verlag, 2017)
This book examines the influence of political ideology in Indonesia’s political parties to address governance issues during the democratic era, 1998–2015. Further, it investigates the policy, agenda and strategies of three ideological parties in Yogyakarta Municipality in coping with public service issues. The three parties are the Indonesian Democratic Party of Struggle (PDIP), the National Mandate Party (PAN) and the Justice and Prosperous Party (PKS).